Young, Britian And The World In The Twentieth Century - Romer, K. Gird (Teaching History: A Journal of Methods, 1999)
Britain and the World in the Twentieth Century is a fine book. It is well written, well organized, and very informative. The work is part of a series titled "International Relations and the Great Powers," a series that includes Japan and the World since 1868, with titles such as France and the World in the Twentieth Century, and The United States and the World in the Twentieth Century forthcoming. The author of Britain and the World in the Twentieth Century, John W. Young, Professor of Politics at the University of Leicester, also wrote Britain and European Unity, 1945-92, Winston Churchill’s Last Campaign, and Cold War Europe. Professor Young has a firm grasp of the material and the ability to present it clearly. The author does presuppose a slight knowledge of twentieth-century English and European history on the part of the reader, but a detailed knowledge is not necessary.